Various stages in the life cycle of syrphid flies (Eristalis tenax; Diptera: Syrphidae) as potential mechanical vectors of pathogens causing mycobacterial infections in pig herds - Fischer, O A; Mátlová, L; Dvorská, L; Svástová, P; Bartos, M; Weston, R T; Pavlík, I (Folia microbiologica, 2006)
We defined the role of the syrphid fly Eristalis tenax in the survival and transmission of mycobacteria in pigs. The conditionally pathogenic mycobacterial (CPM) species Mycobacterium chelonae was isolated from 10 % of liquid dung samples, and both M. chelonae and another CPM species M. fortuitum were isolated from 7 (78 %) of the examined E. tenax larvae collected from the same location. Mycobacteriosis of the lymph nodes of pigs from 3 infected farms was caused by M. avium subsp. avium, M. avium subsp. hominissuis, and M. fortuitum. M. avium subsp. avium and M. avium subsp. hominissuis of identical genotype and serotypes and M. fortuitum were isolated from 7 (1.9 %) larvae, 2 (7.4 %) puparia, and one (1.6 %) imago. The count of colony forming units isolated from larval skin covering (pouch) was higher (p < or = 0.01) than that isolated from the internal organs of larvae. These results showed the potential for E. tenax larvae to spread mycobacteria throughout pig herds and the surrounding environment.
Keywords: Mycobacterium Infections; rozdělení chí kvadrát; Insect Vectors; Chi-Square Distribution; Swine Diseases; Mycobacterium; netuberkulózní mykobakterie; Larva; Animals; nemoci prasat; Mycobacterium avium; hmyz - vektory; Sus scrofa; Diptera; zvířata; Nontuberculous Mycobacteria; mykobakteriózy; larva